2004
DOI: 10.1086/381755
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Bacteriuria in Women with Diabetes: Influence of Metabolic Control

Abstract: We screened 228 women with diabetes for bacteriuria during the period of January 1997 through December 2000 at Pisa General Hospital (Pisa, Italy). A control group of 146 women without diabetes was also evaluated. The frequency of significant bacteriuria was 17.5% (40 of 228) among women with diabetes and 18.5% (27 of 146) among women in the control group. Seven (13.5%) of 52 and 33 (18.8%) of 176 women with type 1 and in type 2 diabetes, respectively, had significant bacteriuria. The presence of higher glycat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
45
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 28 publications
7
45
1
1
Order By: Relevance
“…For diabetes-specific variables, most [1][2][3] but not all [8] studies have found no relationship between glycaemic control and ASB. Chronic complications such as nephropathy and neuropathy have been associated with ASB in type 1 but not type 2 diabetic patients [1,7], a pattern that also holds for longer diabetes duration [7].…”
Section: Discussionmentioning
confidence: 95%
“…For diabetes-specific variables, most [1][2][3] but not all [8] studies have found no relationship between glycaemic control and ASB. Chronic complications such as nephropathy and neuropathy have been associated with ASB in type 1 but not type 2 diabetic patients [1,7], a pattern that also holds for longer diabetes duration [7].…”
Section: Discussionmentioning
confidence: 95%
“…Escherichia coli adhesion to uroepithelial cells is increased in diabetic patients [25], and elevated urinary glucose levels support the growth of bacteria [26]. Lack of metabolic control, as measured by glycated haemoglobin, is a risk factor for bacteriuria [27]. In concordance, control of hyperglycaemia reduced the short-term risk of infectious complications among a population of surgical critically ill patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the decline in renal function in diabetic patients with ASB followed for up to 2 years did not differ from a group with diabetes alone [107]. Diabetic women with ASB are at greater risk of UTI [100] and subsequent hospitalisation with urosepsis [103]. However, there is no evidence that presumptive antibiotic therapy for ASB is beneficial [101,108].…”
Section: Urinary Tract Infectionsmentioning
confidence: 96%
“…A number of predisposing factors for ASB have been reported. In most [99][100][101][102] but not all [103] studies, there is no relationship between glycaemic control and ASB. Chronic complications such as nephropathy and neuropathy have been associated with ASB in type 1 but not type 2 diabetes [99,104], a pattern that holds for longer diabetes duration [104].…”
Section: Urinary Tract Infectionsmentioning
confidence: 97%